Arctic Freshwater Biodiversity Monitoring Plan: Annual Report 2017 and Work Plan 2018. CAFF Monitoring Report No. 26 - Lento, J.; Culp, J.; Goedkoop, W.; Christoffersen, K.; Guðbergsson, G.; Liljaniemi, P.; Sandøy, S.; Whitman, M.; Zimmerman, C. (2018)
The CBMP-Freshwater Plan, developed by the Freshwater Expert Monitoring Group (FEMG) of the CBMP, is the result of work undertaken during workshops held in Uppsala, Sweden (2010) and Fredericton, New Brunswick, Canada (2011). Both workshops included freshwater experts with a broad range of expertise as well as FEMG leads for each Arctic nation (Canada, Sweden, Denmark, Finland, Iceland, Norway, Russia (first workshop only), and USA). These workshops included a preliminary assessment of the spatial and temporal coverage of available monitoring data and identified important elements, i.e., stressors, Focal Ecosystem Components (FECs: biotic or abiotic elements, such as taxa or key abiotic processes, which are ecologically pivotal, charismatic and/or sensitive to changes in biodiversity), parameters, and indicators, to be incorporated into the pan-Arctic Freshwater Plan. The mechanistic link between an environmental or anthropogenic stressor and the FECs was identified through “Impact Hypotheses,” i.e., predictive statements that outline the potential ways in which selected stressors might impact the structure or function of FECs. Preliminary information on the spatial and temporal coverage of available monitoring data for FECs was summarized, and will form the basis for the first assessment of freshwaters in the Arctic.